Impact of warm-up on muscle temperature and athletic performance - Kapnia, A. K.; Dallas, C. N.; Gerodimos, V.; Flouris, A. D. (Research Quarterly for Exercise and Sport, 2023)
Purpose: We performed two studies to investigate: the minute-by-minute changes in muscle temperature following a 20-min warm-up routine (Study-1) and the impact of the typical post-warm-up period of inactivity on the performance of basketball athletes (Study-2).